Velocity pattern of national level female athletes of bangladesh in 200m sprint - Islam, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: During running competition an athlete cannot maintain uniform speed throughout the course in spite of his best possible effect. Velocity pattern indicates the change of velocity at different phases of a race. Purpose of the present study was to analyze the velocity pattern of 200m sprint for National level female junior athletes of Bangladesh. METHODS: Ten junior national level sprinters attending national coaching camp were selected as subjects. The total running distance of 200m was divided into eight equal zones of 25m each. Mean zonal times of all the eight zones for the subjects were measured. From (Distance-time) information of different zones, zonal velocities were calculated and velocity-distance curve was developed for the 200m race. Velocity pattern of the junior level female sprinters for 200m race was analyzed. RESULTS: Results indicated that mean zonal velocity increased from start and the maximum zonal velocity was achieved during (100-125) m zone. Thereafter the zonal velocity gradually decreased for the rest part of the race. The reduction in locomotion velocity was about 10% of the maximum. CONCLUSION: This decrease in velocity in later part of the race might be due the lack of sprint endurance of the athletes. So, the results of this study may be used as diagnostic factors for 200m sprint performance of the subjects.